Effects of Antimony on Rice Growth and Its Existing Forms in Rice Under Arbuscular Mycorrhizal Fungi Environment - Zhou, Min; Li, Xinru; Liu, Xuesong; Mi, Yidong; Fu, Zhiyou; Zhang, Ruiqing; Su, Hailei; Wei, Yuan; Liu, Huifang; Wang, Fanfan (Frontiers in Microbiology, 2022)
Arbuscular mycorrhizal fungi (AMF) can form symbiotic relationships with most terrestrial plants and regulate the uptake and distribution of antimony (Sb) in rice. The effect of AMF on the uptake and transport of Sb in rice was observed using pot experiments in the greenhouse. The results showed that AMF inoculation increased the contact area between roots and metals, and changed the physical and chemical properties of the soil, leading to more Sb entering various parts of the rice, especially at an Sb concentration of 1200 mg/kg. The increase in metal toxicity further led to a decrease in the rice chlorophyll content, which directly resulted in a 22.7% decrease in aboveground biomass, 21.7% in underground biomass, and 11.3% in grain biomass. In addition, the antioxidant enzyme results showed that inoculation of AMF decreased 22.3% in superoxide dismutase, 9.9% in catalase, and 20.7% in peroxidase compared to the non-inoculation groups, further verifying the negative synergistic effect of AMF inoculation on the uptake of Sb in rice. The present study demonstrated the effect of AMF on the uptake and transport of Sb in the soil–rice system, facilitating future research on the related mechanism in the soil–rice system under Sb stress.